Carbon–carbon bond cleavage and rearrangement of benzene by a trinuclear titanium hydride - Hu, Shaowei; Shima, Takanori; Hou, Zhaomin (Nature (London), 2014)
A trinuclear titanium polyhydride complex can be used to cleave carbon–carbon bonds in benzene and transform the benzene ring, suggesting that multinuclear titanium hydrides could be used to activate aromatic molecules. Benzene C–C bond breakage made simpler Carbon–carbon bond cleavage by transition metals is central to chemical synthesis, petroleum chemistry and biological systems. Until now cleavage of benzene by a transition metal complex has not been available to synthetic chemists, but here Zhaomin Hou and colleagues report the first example of carbon–carbon bond cleavage and rearrangement of benzene by a well-defined molecular system — a trinuclear titanium polyhydride complex. The benzene ring is transformed sequentially to a methylcyclopentenyl and a 2-methylpentenyl species via the cleavage of the aromatic carbon skeleton at the multi-titanium sites. This work suggests that multinuclear titanium hydrides could be used as a platform for the activation of aromatic molecules, and may facilitate the design of new catalysts for the transformation of inactive aromatics. The cleavage of carbon−carbon (C−C) bonds by transition metals is of great interest, especially as this transformation can be used to produce fuels and other industrially important chemicals from natural resources such as petroleum and biomass. Carbon−carbon bonds are quite stable and are consequently unreactive under many reaction conditions. In the industrial naphtha hydrocracking process, the aromatic carbon skeleton of benzene can be transformed to methylcyclopentane and acyclic saturated hydrocarbons through C−C bond cleavage and rearrangement on the surfaces of solid catalysts 1 , 2 , 3 , 4 , 5 , 6 . However, these chemical transformations usually require high temperatures and are fairly non-selective. Microorganisms can degrade aromatic compounds under ambient conditions, but the mechanistic details are not known and are difficult to mimic 7 . Several transition metal complexes have been reported to cleave C−C bonds in a selective fashion in special circumstances, such as relief of ring strain, formation of an aromatic system, chelation-assisted cyclometallation and β-carbon elimination 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 . However, the cleavage of benzene by a transition metal complex has not been reported 16 , 17 , 18 , 19 . Here we report the C−C bond cleavage and rearrangement of benzene by a trinuclear titanium polyhydride complex. The benzene ring is transformed sequentially to a methylcyclopentenyl and a 2-methylpentenyl species through the cleavage of the aromatic carbon skeleton at the multi-titanium sites. Our results suggest that multinuclear titanium hydrides could serve as a unique platform for the activation of aromatic molecules, and may facilitate the design of new catalysts for the transformation of inactive aromatics.